Built-in capacitance sensor for control rod position measurement in NHR-200 with PEEK material. (February 2019) - Hu, Guang; Liu, Qianfeng; Zhang, Huang; Qin, Benke; Bo, Hanliang
Highlights: PEEK are introduced as the control rod guide rod material. Measurement resolution of the BCRMS is as high as ±7.09 mm. The built models and BCRMS are proved to be an efficient solution to measure the control rod position in NHR-200. Abstract: The accurate control rod position measurement is crucial to ensure the reactor safety and reliability. Based on the variations of equivalent electrical permittivity with different control rod positions in NHR-200, the built-in capacitance control rod position measurement system (BCRMS) has been successfully used for the PEEK material control rod guide rod due to its advantages of non-invasion, low-cost, high reliability and non-radiation. And a novel method is proposed to calibrate the built-in capacitance control rod position sensor (BCRS) based on the grating linear displacement measuring probe. The BRCMS was experimentally tested on the horizontal test facilities. In addition, Capacitances obtained by the built electric theoretical model and FEM analysis were compared with experiment results to verify the built models. Meanwhile, measurement resolution of the newly designed BCRMS is as high as ±7.09 mm. Errors caused by the eccentricity and sensor end effects are analyzed to be in the reasonable range. The built models and newly designed BCRMS are proved to be an effective solution to measure the control rod position in NHR-200.